De ruptures en canon - Côme Martin (Sillages Critiques)
Amongst comics created before and after 1900, historiography often picks Little Nemo in Slumberland, Krazy Kat and Yellow Kid as being part of canonical history and elevates these three works to the rank of classics. However, careful analysis shows how these comics were in dissonance with their contemporaries: by placing the concept of tearing at the centre of their formal aesthetic and by exploring it as a thematic subject, they are far from being a representative corpus of the times. I thus study how the consideration of these comics has evolved from their creation until today, and show how they are objects both unique and representative of American comics as a whole.